An empirical study of assurance in the UK government major projects portfolio: from data to recommendations, to action or inaction - Vo, Hang; Kirkham, Richard John; Williams, Terry Mervyn; Howells, Amanda; Forster, Rick; Cooke-Davies, Terry (Emerald, 2024)
Purpose: Effective and robust governance of major projects and programmes in the public sector is crucial to the accountability of the state and the transparency of state spending. The theoretical discourse on governance, in the context of projects and programmes, is not fully mature, although is now sufficiently well developed to warrant an increased scholarly focus on practice. This paper aims to contribute to the empirical literature through a study of assurance routines in the UK Government Major Projects Portfolio (GMPP). Design/methodology/approach: A framework analysis approach to the evaluation of a subset of GMPP database generates original insights into (1) the framing of assurance review recommendations, (2) the treatment of assurance review data and (3) the subsequent tracking of the implementation of actions arising from the assurance review process. Findings: The analysis reveals that the “delivery confidence” of the major projects and programmes included in this study improves during the time that they are assured on the GMPP. This would suggest that “enhanced” governance routines are desirable in programmes and projects that exhibit high degrees of complexity and scale. Originality/value: The research findings contribute to the wider conversations in this journal and elsewhere on project governance routines and governance-as-practice in the context of government and public services.
Keywords: project governance; project assurance; review recommendations; delivery confidence assessment; government